Altered gene expression levels of genes related to muscle function in adults with cerebral palsy. (June 2022) - Pingel, Jessica; Vandenrijt, Jasper; Kampmann, Marie-Louise; Andersen, Jeppe Dyrberg
Highlights: Significant different gene expression levels were observed between adults with CP and typical developing (TD) adults in various genes. Differences in muscle contraction (MYH1 & MYBPC2), mitochondrial function (ATP5J, CYCS & NDUFB6), and calcium handling (CAMK2B & ATP2A). Variant frequencies of the mtDNA and the mitochondrial content did not differ when comparing muscle tissue from adult CP and TD individuals. The ion levels of Ca 2+, Na +, K + and Cl − were significantly different in adults with CP when compared to TD adults. Abstract: Cerebral palsy (CP) is the most common cause of movement disorders in children. Next generation sequencing (NGS) studies have previously shown that expression levels are fundamentally different in children with CP compared to typically developing (TD). However, given that children are in full development, we might expect gene expression levels to change once maturity is reached. Therefore, the main purpose of this study was to investigate gene expression levels of 93 target genes in adults with CP using NGS on muscle biopsies of the gastrocnemius, taken from 22 participants (n = 12 adults with CP; n = 10 TD adults). Subsequently, we carried out NGS of the mitochondrial genome to identify mtDNA variants, and additionally we studied the mitochondrial content using transmission electron microscopy images of the gastrocnemius muscle. Finally, we compared systemic ion levels between TD adults and adults with CP. Differential gene expression levels were found in genes involved in muscle contraction ( MYH1 and MYBPC2 ), mitochondrial function kATP5J, CYCS and NDUFB6 ), calcium handling ( CAMK2B and ATP2A ), metabolism (LPL), muscle signaling ( MYC, CREB1, ACVR2B, LMNA and TRIM54 ), and ECM ( TNC ). There was no statistical significant difference between CP and TD for mtDNA variant frequencies and mitochondrial content. The ion levels of Ca 2+, Na + and K + were statistically significantly reduced while the Cl − levels were significant increased in adults with CP compared to TD adults. These results highlight that most transcriptional differences are related to muscle function in adults with CP and that mitochondrial function might be altered but not mitochondrial content.